LEARNING STRATEGIES OF FASTRACK STUDENTS OF THE ISLAMIC EDUCATION MANAGEMENT STUDY PROGRAM AT MAULANA MALIK IBRAHIM STATE ISLAMIC UNIVERSITY MALANG - SAYYIDA, SAYYIDATUL QORYAH; Munir, Munirul Abidin (An Natiq, 2024)
The demands of studying in college require students to learn to be more independent and disciplined in managing their time. The progress of science and technology is a challenge for universities as centers of scientific development accompanied by global competition, which requires a fast track approach. UIN Maulana Malik Ibrahim Malang is one of the Islamic Universities in Indonesia that organizes the fastrack program. This program was held with the aim of providing facilities for undergraduate students who excel in academics, English, and who have high motivation to continue their master's degree, with the hope of increasing the number of superior students in the master's program and increasing scientific publications. Fastrack is an accelerated education program that allows students to complete a degree in less time than traditional programs. The speed required can pose its own challenges in terms of time management, understanding, material and study strategies. This research aims to describe the learning strategies of Fastrack students and the obstacles and challenges they face. The research method used is descriptive qualitative. Data collection techniques include distributing questionnaires, interviews, observation and documentation. The results of the research identified fastrack students' learning strategies, namely discipline, planning, collaboration and motivation. It was also found that the obstacles and challenges faced by Fastrack students were scheduling conflicts between undergraduate and graduate program schedules, overloaded assignments, and students lacking self-confidence due to lack of learning experience.